Characterization of calcium carbonate sorbent particle in furnace environment - Lee, Kang Soo; Jung, Jae Hee; Keel, Sang In; Yun, Jin Han; Min, Tai Jin; Kim, Sang Soo (ELSEVIER SCIENCE BV, 2012)
The oxy-fuel combustion system is a promising technology to control CO2 and NOx emissions. Furthermore. sulfation reaction mechanism under CO2-rich atmospheric condition in a furnace may lead to in-furnace desulfurization. In the present study, we evaluated characteristics of calcium carbonate (CaCO3) sorbent particles under different atmospheric conditions. To examine the physical/chemical characteristics of CaCO3, which is used as a sorbent particle for in-furnace desulfurization in the oxy-fuel combustion system, they were injected into high temperature drop tube furnace (DTF). Experiments were conducted at varying temperatures, residence times, and atmospheric conditions in a reactor. To evaluate the aerosolizing characteristics of the CaCO3 sorbent particle, changes in the size distribution and total particle concentration between the DTF inlet and outlet were measured. Structural changes (e.g., porosity, grain size, and morphology) of the calcined sorbent particles were estimated by BET/BJH, XRD, and SEM analyses. It was shown that sorbent particles rapidly calcined and sintered in the air atmosphere, whereas calcination was delayed in the CO2 atmosphere due to the higher CO2 partial pressure. Instead, the sintering effect was dominant in the CO2 atmosphere early in the reaction. Based on the SEM images, it was shown that the reactions of sorbent particles could be explained as a grain-subgrain structure model in both the air and CO2 atmospheres. Crown Copyright (C) 2012 Published by Elsevier B.V. All rights reserved.
Keywords: O-2/CO2 COAL COMBUSTION; DIRECT SULFATION; CALCINATION; LIMESTONE; TECHNOLOGY; REDUCTION; MECHANISM; CAPTURE; NOX